ANALISIS PREFERENSI SISWA MELANJUTKAN KESMP SANTA MARIA PEKANBARU T.P. 2014/2015 - Fransisca MeiAnanik K Fransisca MeiAnanik K; Tri Umari Tri Umari; Zulfa ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The objectives of this research one : 1. To analyze internalfactors that become students preference to SMP Santa Mari Pekanbaru. 2. To analyze the external factors that become the students preference to SMP Santa Mari Pekanbaru. 3. To know category of internal preference. 4. To know category of external preference. The method that has been used in this research was random sampling. The results of this research are: 1. The internal factors that become the students preference to SMP is the students want to continue to SMA and suitable with the interest 93,79%. 2. The internal factor that became the students preference to SMP based of the knowledge have been learnt in SD 89,66%. 3. Category of internal preference that high is 49,7%, medium is 44,1% and low is 6,2%. 4. Category of eksternal preference that high is 60,7%, medium 24% dan low is 14,5%. Keywords : Preferences